Exposure Of Media Information And The Role Of Family Planning Field Officer Toward Use Of Long-Term Contraception Methods: Analysis Of 2017 Indonesia Demography And Health Survey - Gustina, Erni; Matahari, Ratu; Sulistiawan, Dedik; Oktafia, Rina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Long-term contraceptive methods (LTCM) are highly effective in preventing unwanted pregnancies. However, of all users of modern methods in the Special Region of Yogyakarta, only 37.19% used LCTM. The socialization of contraceptive use through the media and family planning field officers has a strategic role in encouraging the use of LCTM. The aim of this study to analyze the exposure of information media and the role of family planning field officers using LTCM. The study was conducted by analyzing secondary data of the Indonesian Demographic and Health Survey in 2017. The sample size of 248 Eligible women. Hypothesis testing uses Fisher's Exact Test statistics. Multiple logistic regression used to produce an adjusted odds ratio. Most of the respondents have never been exposed to family planning information from radio (83.71%) and magazines (77.59%). Only 2% of respondents stated that they had received information and education from family planning field officers. Multivariable analysis showed that there was no relationship between exposure to radio information media (AOR = 0.79; CI = 0.37-1.71; p-value = 0.558), television (AOR = 1.16; CI = 0.65 -2.08; p-value = 0.616), magazines (AOR = 1.80; CI = 0.91-3.58; p-value = 0.093) and the role of family planning field officer (AOR = 0.92; CI = 0, 14-6.02; p-value = 0.929) with the use of LCTM. Eligible women who are exposed to family planning information through radio, television, magazines and who have received communication, education and information by family planning field officer have a higher probability of usingLTCMalthough it is not statistically significant. The use of other media, such as new media can be taken into consideration in promoting the use of LTCM. Abstrak: Metode kontrasepsi jangka panjang (MKJP) terbukti memiliki efektivitas tinggi dalam mencegah kehamilan. Meskipun demikian, dari seluruh pengguna metode modern di Daerah Istimewa Yogyakarta, hanya sebesar 37,19% yang menggunakan MKJP. Sosialisasi penggunaan kontrasepsi melalui media dan petugas lapangan keluarga berencana (PLKB) memiliki peran strategis dalam mendorong penggunaan MKJP. Tujuan penelitian menganalisis keterpaparan media informasi dan peran PLKB dengan penggunaan MKJP.Penelitian menganalisis data sekunder Survei Demografi dan Kesehatan Indonesia (SDKI) 2017. Besar sampel 248 WanitaUsiaSubur di DIY. Pengujian hipotesis menggunakan statistik Fisher’s Exact Test.Regresi logistik berganda digunakan untuk menghasilkan nilai adjusted odds ratio. Sebagian besar responden tidak  pernah terpapar informasi KB dari radio (83,71%) dan majalah (77,59%). Hanya 2% responden menyatakan pernah mendapatkan KIE dari PLKB. Analisis multi variabel menunjukan tidak terdapat hubungan antara keterpaparan media informasi radio (AOR=0,79; CI=0,37-1,71; p-value= 0,558), televisi (AOR=1,16; CI=0,65-2,08; p-value= 0,616), majalah (AOR=1,80; CI=0,91-3,58; p-value= 0,093) dan peran PLKB (AOR=0,92; CI=0,14-6,02; p-value= 0,929) dengan penggunaan MKJP.WUS yang terpapar informasi KB melalui media radio, televisi, majalah dan pernah mendapatkan komunikasi, edukasi dan informasi oleh PLKB memiliki probabiltas yang lebih tinggi untuk menggunakan MKJP meskipun tidak signifikan secara statistik. Penggunaan media lain seperti new media bisa di jadikan pertimbangan dalam mempromosikan penggunaan MKJP.